IN VITRO AND IN VIVO SUSCEPTIBILITY OF MASTITIS PATHOGENS ISOLATED FROM BOVIN MASTITIS TO ANTIMICROBIAL DRUGS - A. Yass , A. (The Iraqi Journal of Veterinary Medicine, 1992)
The in vitro sensitivity testing of mastitis pathogens, associated with udder infections in cows, against 12 chemotherapeutic agents, showed that all strains (100%) tested are sensitive to gentamicin. 96.12% to 70.87% of the isolates are sensitive to kanamycin, erythromycin, chloramphenicol, cloxacillin, streptomycin, tetracycline and ampicillin. All strains are resistant to colistin (except for E. coli) and sulfa drugs. Multimast was found to be most efficious in the treatment of bovine mastitis (89.28%), followed by Multiject Imm, Kanamast and Neomastitar (76.92%, 74.19% and 68.00%) respectively.